2020
DOI: 10.1177/0300891620951626
|View full text |Cite
|
Sign up to set email alerts
|

A possible future for anaesthesia in breast surgery: thoracic paravertebral block and awake surgery. A prospective observational study

Abstract: Introduction: Quadrantectomy is a surgical procedure traditionally performed under general anaesthesia with intraoperative and postoperative opioid-based analgesia. The use of locoregional anaesthesia techniques in breast surgery has become widespread and allows excellent management of intraoperative and postoperative pain with reduced opioid consumption. We chose thoracic paravertebral block as regional anaesthesia technique in breast surgery to investigate the possibility of carrying out this surgery with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In our hospital the TPV block has been performed for many years for both mastectomies and quadrantectomies, therefore, its effectiveness has been extensively con rmed even for interventions with awake patients [7,21,34].…”
Section: Discussionmentioning
confidence: 99%
“…In our hospital the TPV block has been performed for many years for both mastectomies and quadrantectomies, therefore, its effectiveness has been extensively con rmed even for interventions with awake patients [7,21,34].…”
Section: Discussionmentioning
confidence: 99%
“…This study reported no morbidity in the form of hematoma, wound infection or skin ap necrosis. A prospective observational series of patients undergoing breast conserving surgery under a paravertebral block and mild sedation reported successful outcomes, including no need for intraoperative or postoperative opioids [27]. A survey of breast surgeons noted that approximately two thirds of respondents considered breast surgery under local anesthesia to be well-tolerated amongst older women [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, another study demonstrated no significant difference in disease recurrence and survival between the sOLV and mOLV methods ( 34 ). Meanwhile, a study on awake breast cancer surgery suggested that both extrathoracic cancer cases and lung cancer sOLV cases had shorter operative time and length of hospital stay ( 35 , 36 ). Additionally, a case series presented about successful esophagectomy wherein the thoracic part was performed under spontaneous ventilation ( 37 ).…”
Section: Effects Of Nits On Cancermentioning
confidence: 99%